2015
DOI: 10.1159/000433553
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Faced by Patients Suffering from Total Bilateral Vestibular Loss

Abstract: A unilateral sudden loss of function generates intense and frightening symptoms urging patients to see a doctor. Generally, the symptoms and signs of the deficit are so obvious that doctors make the diagnosis quickly. The situation is quite different if the deficit is gradual and affects both sides. To better understand the difficulties faced by patients suffering from total bilateral vestibular loss, 19 subjects were interviewed in a semistructured talk. The discussion focused on five main topics: (1) symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
0
22
0
5
Order By: Relevance
“…A high level of interrater reliability was reached on the full article selection with a Cohen’s kappa of 0.98. Finally, 1,385 unique patients from 41 clinical studies and 86 patients from 47 case reports were included ( 2 , 5 , 14 99 ). The characteristics of these articles can be found in Tables A1 and A2 in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of interrater reliability was reached on the full article selection with a Cohen’s kappa of 0.98. Finally, 1,385 unique patients from 41 clinical studies and 86 patients from 47 case reports were included ( 2 , 5 , 14 99 ). The characteristics of these articles can be found in Tables A1 and A2 in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms for diagnosis include unsteadiness when walking or standing, movement-induced blurred vision/oscillopsia during walking or quick head movements, or worsening of unsteadiness on uneven ground and/or darkness ( 1 , 3 , 4 ). However, clinical experience and current literature point to a wider variety of symptoms ( 5 ). For example, many patients report a negative impact on physical and social functioning, and compromised cognitive abilities ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the picture is completely different for other conditions. The handicap suffered by patients with a complete loss of the vestibular function is significantly underestimated and the pathway to diagnosis is full of hurdles [46,64]. However, recent studies have unambiguously revealed that the complete loss of the vestibular function has a dramatic impact on the quality of life of affected patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to develop a viable prosthetic device to restore vestibular function have gained traction and have been evidenced to improve VOR, postural stability and gait speed in humans [14][15][16]. The successful development of a prosthetic device that restores vestibular function would confer great benefit on patients; improving their quality of life and reducing the frequency of falls and hospital visits [17]. The potential economic value in such a device is noteworthy; a recent study conducted a sensitivity analysis, predicting that a device recovering 75% of vestibular function would have a cost-utility of $37986/quality-adjusted life year (QALY), well below the $50,000/QALY willingness-to-pay threshold at which medical interventions are considered to be 'highly cost-effective' in the US [18].…”
Section: Vestibular Dysfunctionmentioning
confidence: 99%